2021
DOI: 10.1101/2021.11.05.467408
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

3CAC: improving the classification of phages and plasmids in metagenomic assemblies using assembly graphs

Abstract: Bacteriophages and plasmids usually coexist with their host bacteria in microbial communities and play important roles in microbial evolution. Accurately identifying sequence contigs as phages, plasmids, and bacterial chromosomes in mixed metagenomic assemblies is critical for further unravelling their functions. Many classification tools have been developed for identifying either phages or plasmids in metagenomic assemblies. However, only two classifiers, PPR-Meta and viralVerify, were proposed to simultaneou… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The latter has been used as the basis for DeepVirFinder ( Ren et al, 2020 ), a deep learning method that uses convolutional neural networks, capable of detecting viral signals in very short contigs (<5,000 bps). Other recently developed deep learning tools include 3CAC ( Pu and Shamir, 2022 ), a combined predictor of phages and bacterial plasmids, the bacteriophage-specific INHERIT ( Bai et al, 2022 ), virSearcher ( Liu et al, 2022 ), PHAMB ( Johansen et al, 2022 ), Seeker ( Auslander et al, 2020 ) and PhaMer ( Shang et al, 2022 ) predictors and DeepMicrobeFinder ( Hou et al, 2021 ), which classifies metagenomic contigs into five sequence classes (prokaryotic genomes, eukaryotic genomes, plasmids, prokaryotic-infecting viruses and eukaryotic-infecting viruses) with a reported accuracy of over 90% for viral contigs.…”
Section: Metagenomic Analysis and Workflowsmentioning
confidence: 99%
“…The latter has been used as the basis for DeepVirFinder ( Ren et al, 2020 ), a deep learning method that uses convolutional neural networks, capable of detecting viral signals in very short contigs (<5,000 bps). Other recently developed deep learning tools include 3CAC ( Pu and Shamir, 2022 ), a combined predictor of phages and bacterial plasmids, the bacteriophage-specific INHERIT ( Bai et al, 2022 ), virSearcher ( Liu et al, 2022 ), PHAMB ( Johansen et al, 2022 ), Seeker ( Auslander et al, 2020 ) and PhaMer ( Shang et al, 2022 ) predictors and DeepMicrobeFinder ( Hou et al, 2021 ), which classifies metagenomic contigs into five sequence classes (prokaryotic genomes, eukaryotic genomes, plasmids, prokaryotic-infecting viruses and eukaryotic-infecting viruses) with a reported accuracy of over 90% for viral contigs.…”
Section: Metagenomic Analysis and Workflowsmentioning
confidence: 99%
“…Most of the existing classifiers take contigs as input and classify each of them independently based on its sequence. Our recent work on three-class classification demonstrated that neighboring contigs in an assembly graph are more likely to come from the same class and thus the adjacency information in the graph can be used to improve the classification [30]. Therefore, here too we exploit the assembly graph to improve the initial classification by the following two steps.…”
Section: Refining the Classification Using The Assembly Graphmentioning
confidence: 99%
“…Plasmid classifiers, such as cBar [43], PlasFlow [15], PlasClass [27], and Deeplasmid [1], were developed to separate plasmids from prokaryotes. As both phages and plasmids are commonly found in microbial communities, three-class classifiers, such as PPR-Meta [7], viralVerify [2], and 3CAC [30], were proposed to simultaneously identify phages, plasmids, and prokaryotes from metagenome assemblies. On the other hand, microbial eukaryotes, such as fungi and protozoa, are integral components of natural microbial communities but were commonly ignored or misclassified as prokaryotes in most metagenome analyses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent method 3CAC [24] introduced the idea that the classification of a contig can be improved from the knowledge of the classification of the neighbouring contigs in the assembly graph. Most current assembly programs [7, 28] output an assembly graph containing final contigs as nodes and possible connections between them supported by sequencing data as edges.…”
Section: Introductionmentioning
confidence: 99%